Dynamic simulation of centrifugal compressors in a process environment - Razak, A. M. Y. (Cranfield University, 1984)
The recent developments in process plant design have made it desirable that a better understanding of transient compressor performance within the process plant be gained. The model outlined in this thesis is capable of representing most types of process plants. Further the number of degress of freedom, plus the dynamic flexibility of a poly- tropic analysis allow any system transient to be simulated, including compressor surge. A computer program has been developed from the model and validated using a small centrifugal compressor. The results showing successful simulation of compressor transient behaviour (including surge) are given. The model was then applied to study the transient behaviour of a natural Gas Transmission station. The model successfully highlighted compressor surge problems under certain operative conditions. This surge phenomenon is present in the trans- mission station and a possible solution to the problem was suggested due to the better understanding of dynamic response of station.